Photon shielding competence of concrete doped CuO for gamma shielding applications - Hudu, Salisu; Mustapha, Idris M.; Bello, Sulayman M.; Halimatu, Abdullahi S.; James, Iwa S.; Aisha, Mohammed A.; Ubaidullah, Ahmad (Journal of Physics: Theories and Applications, 2024)
In this study, photon attenuation parameters of concrete doped CuO, were determined and their application as shielding material were discussed. The WinXCOM software was used to determine the mass attenuation coefficient (MAC) of the concrete doped CuO samples (0, 20, 40 60 and 100 wt% CuO content) for the energy range (0.015-15MeV). The linear attenuation coefficient, half value layer (HVL), mean free path (MFP), and effective atomic number (Zeff) were calculated from the MAC values. The MAC values of the samples decreases rapidly up to 0.12 MeV, and beyond 0.12 MeV, Compton scattering becomes effective at intermediate energies. The LAC value vary with energy in similar way as MAC. The calculated HVL and MFP were observe to  decline  as  the  CuO doping  of  the  glasses  increased  which  accounts  for  the  three  photon interaction mechanisms effectiveness in the variation of HVL and MFP values with energy. The Zeff shows minimal variation as the energy increases in all the concrete doped CuO samples. It can be concluded that doping CuO with concrete can greatly enhance the gamma shielding ability of the sample.